Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1982
DOI: 10.1088/0022-3700/15/19/015
|View full text |Cite
|
Sign up to set email alerts
|

Penning and associative ionisation of highly excited rubidium atoms

Abstract: Penning and associative ionisation of highly excited rubidium atoms View the table of contents for this issue, or go to the journal homepage for more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(25 citation statements)
references
References 18 publications
5
20
0
Order By: Relevance
“…The indetermination on K shows, as expected, that this experiment is not the best way to investigate process (14); a simple way to perform this experiment would be to excite by two photon the transition 3s-4d and then detect the sensitized fluorescence 4f-3d.…”
Section: Fsupporting
confidence: 52%
See 1 more Smart Citation
“…The indetermination on K shows, as expected, that this experiment is not the best way to investigate process (14); a simple way to perform this experiment would be to excite by two photon the transition 3s-4d and then detect the sensitized fluorescence 4f-3d.…”
Section: Fsupporting
confidence: 52%
“…The equations are therefore where K and K ' are the rate coefficients of process (14); they are related to each other /25/ through the level degeneracy K/K' = (g4f/g4d)e~p(-&/kT) = 1.26. The solution of eq.…”
Section: -An Update Experiments In Sodiummentioning
confidence: 99%
“…The theoretical model involves the most important collisional and radiative interactions under the experimental conditions of Barbier et al [5]. Also, a comparison between the theoretical results and the experimental measurements, of Cheret et al [1] for the ion current of the atomic ion and molecular ion, is considered in the present work.…”
Section: Introductionmentioning
confidence: 95%
“…On the other hand, resonant laser excitation has played a vital role in coupling energy into vapor. Therefore the reaction of a dense ru-bidium vapour, resonantly irradiated by a CW laser, has been the subject of a number of investigations during in recent years [1][2][3][4][5][6][7]. These studies have shown that a large variety of mechanisms take place in the excited media.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation